1998
DOI: 10.1002/(sici)1097-0215(19980302)75:5<694::aid-ijc6>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Nation-wide breast cancer screening in The Netherlands: Results of initial and subsequent screening 1990–1995

Abstract: Based on an extensive cost‐effectiveness analysis, the Dutch nation‐wide breast cancer screening programme started in 1990, providing a biennial screen examination to women aged 50 to 69 years. The programme is monitored by the National Evaluation Team, which annually collects tabulated regional evaluation data to determine performance indicators. This study presents (trends in) the outcomes of initial and subsequent screening rounds, 1990–1995, and compares them to the predictions of the cost‐effectiveness‐an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
5
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 17 publications
3
63
5
1
Order By: Relevance
“…8 The current result may at least partially indicate differences in diagnostic and treatment practices within and/or outside the organised screening. Noteworthy, studies on organised mammography from the Netherlands have reported low recall rates (0.7-1.3%), 23,24 reduced rates of advanced cancers, 25 and similar impact on the breast cancer mortality as the current study. 13 Thus it is possible that indicators of screening performance may be of limited use in predicting the quantity of mortality reduction.…”
Section: Comparison Of Results To Other Studiessupporting
confidence: 61%
“…8 The current result may at least partially indicate differences in diagnostic and treatment practices within and/or outside the organised screening. Noteworthy, studies on organised mammography from the Netherlands have reported low recall rates (0.7-1.3%), 23,24 reduced rates of advanced cancers, 25 and similar impact on the breast cancer mortality as the current study. 13 Thus it is possible that indicators of screening performance may be of limited use in predicting the quantity of mortality reduction.…”
Section: Comparison Of Results To Other Studiessupporting
confidence: 61%
“…Year 1993 was considered the starting point of breast cancer screening, which was fully implemented in 1996 (Fracheboud et al, 1998(Fracheboud et al, , 2004. Calculation of risk for the ipsilateral and contralateral second breast cancer was performed using only patients with information on laterality of first BCIS and second breast cancer (excluded for this analysis n ¼ 52).…”
Section: Methodsmentioning
confidence: 99%
“…At the time it was estimated that it would reduce breast cancer mortality in the total female population by 17% (Koning et al, 1995b). Early findings up to 1996 with regard to participation, detection of breast cancers and stage distribution of screen-detected cancers were rather favourable, especially in initial screens (Koning et al, 1995a;Fracheboud et al, 1998). However, the interpretation of the results was hampered by the lack of information on interval cancers.…”
mentioning
confidence: 99%